Application of treating fluid as additive for improving bending resistance of formed foil and preparation method of bending-resistant formed foil

By using a specific water-soluble polymer material treatment solution to form a polymer film, the problem of high brittleness of the foil is solved, its torsion resistance and specific capacitance are improved, and it is suitable for capacitor manufacturing, reducing production costs and poor capacitor phenomena.

CN119243305APending Publication Date: 2025-01-03RUYUAN YAO AUTONOMOUS COUNTY DONGYANGGUANG FORMED FOIL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411359303.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The high brittleness of the foil is caused by prone to cracking and foil breaking during the capacitor manufacturing process. In addition, increasing the thickness to improve the tortuous resistance will increase production costs and hinder the development of capacitor miniaturization.

Method used

The foil is processed using a treatment liquid containing water-soluble polymer materials of a specific mass concentration and type to form a polymer film, improving its torsion resistance and maintaining high specific capacity.

Benefits of technology

The torsion resistance of the foil is significantly improved, cracking or fracture in cutting, winding, nailing and other processes is reduced, and the treatment liquid can be dissolved in the electrolyte, without affecting the performance of the capacitor and avoiding thickness changes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of formed foils, and particularly relates to application of a treating fluid as an additive for improving the bending resistance of a formed foil and a preparation method of the bending-resistant formed foil. The treating fluid comprises a water-soluble polymer material, and the water-soluble polymer material is selected from one or more of polyethylene glycol, polyvinyl alcohol, hydroxypropyl methyl cellulose or polyethylene glycol borate; the mass concentration of the water-soluble polymer material in the treating fluid is 0.1-0.7%. The treating fluid can greatly improve the bending resistance of the formed foil and maintain the high specific volume of the formed foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemically formed foils, and more specifically, relates to the application of a treatment liquid as an additive for improving the bending resistance of chemically formed foils and a method for preparing the bending-resistant chemically formed foils. Background Art

[0002] Aluminum electrolytic capacitors are energy storage components widely used in the electronics and electrical industry, and chemical foil is one of the important raw materials for aluminum electrolytic capacitors. The structural characteristics of chemical foil determine the electrical properties of aluminum electrolytic capacitors. Chemical foil is a product obtained by electrochemically or chemically corroding a special high-purity aluminum foil to expand its surface area, and then forming an oxide film (aluminum oxide) on the surface through electrochemical formation. According to the voltage, chemical foil is generally divided into four types: extremely low voltage, low voltage, medium and high voltage, and high voltage; according to the purpose, chemical foil can be divided into positive foil, negative foil or conductive foil. At present, the production process of chemical foil can generally be summarized as: aluminum foil → pre-treatment → corrosion treatment → post-treatment → chemical treatment → obtain chemical foil. The chemical treatment uses multi-stage power supply to generate a dense aluminum oxide film on the surface of the corroded foil, thereby obtaining the chemical foil.

[0003] The aluminum oxide film covered on the surface of the chemical foil has high hardness and poor toughness, and has high brittleness and is easy to crack when bent. When the chemical foil is applied to capacitor manufacturing, undesirable phenomena such as cracking and foil breaking often occur in the processes such as cutting, winding, and nailing. And if the chemical foil with high specific capacity is pursued, its brittleness is also higher, which is not conducive to practical application. In view of this problem, most of the bending performance of the chemical foil is improved by increasing the thickness of the chemical foil, that is, the thickness of the chemical foil is increased while ensuring that the specific capacity remains unchanged, thereby improving the brittleness of the chemical foil. However, the increase in the thickness of the chemical foil has brought about an increase in production costs, and is not conducive to the miniaturization development of capacitors. Therefore, how to improve the bending resistance of the chemical foil while ensuring the high specific capacity of the chemical foil has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art chemically formed foil, such as high brittleness and poor bending resistance, and to provide an application of a treatment liquid as an additive for improving the bending resistance of the chemically formed foil.

[0005] Another object of the present invention is to provide a method for preparing a flexural-resistant formed foil.

[0006] Another object of the present invention is to provide a flexural-resistant foil prepared by the preparation method.

[0007] Another object of the present invention is to provide an aluminum electrolytic capacitor.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] The invention provides application of a treatment liquid as an additive for improving the bending resistance of a chemically formed foil. The treatment liquid comprises a water-soluble polymer material, and the water-soluble polymer material is selected from one or more of polyethylene glycol, polyvinyl alcohol, hydroxypropyl methylcellulose or polyethylene glycol borate; the mass concentration of the water-soluble polymer material in the treatment liquid is 0.1-0.7%.

[0010] The present invention uses a treatment liquid containing a specific mass concentration and a specific type of water-soluble polymer material to treat the chemical foil. After the treatment, a smooth polymer film can be formed on the surface of the chemical foil, thereby reducing the brittleness of the chemical foil, greatly improving its bending resistance and maintaining the high specific volume of the chemical foil. The improvement of the bending resistance can reduce the occurrence of cracking or breaking caused by cutting, winding, nailing and other processes in the subsequent capacitor manufacturing process. In addition, the treatment liquid can be dissolved in the electrolyte in the subsequent capacitor manufacturing process. As a component of the electrolyte, it does not affect the performance of the electrolyte in the capacitor, and will not cause a significant change in the thickness of the chemical foil.

[0011] Through research, the inventors found that when the concentration of the treatment liquid is too high, although it can improve the bending resistance of the chemical foil, it will also cause blockage of the pores of the chemical foil, ultimately leading to a decrease in its specific volume and reducing the quality of the chemical foil; when the concentration of the treatment liquid is too low, it has no obvious effect on the bending resistance of the chemical foil.

[0012] The use of the treatment liquid of the present invention as an additive for improving the bending resistance of chemically formed foil has the same effect on any chemically formed foil, including but not limited to ultra-low pressure chemically formed foil, low pressure chemically formed foil, high pressure chemically formed foil, medium and high pressure chemically formed foil, etc.

[0013] Polyethylene glycol is also called polyoxyethylene, polyethylene oxide or polyglycol, and its molecular formula is H(OCH2CH2-) n -OH, wherein n is the number of repetitions of the repeating unit in the molecular formula brackets. The polyethylene glycol of the present invention is a linear long-chain polymer having a molecular weight greater than 200 Da. Preferably, the molecular weight of the polyethylene glycol is 200 to 1×10 5 More preferably, the average molecular weight of the polyethylene glycol is 8000 to 1×10 5 Da.

[0014] The molecular formula of polyvinyl alcohol is [C2H4O] n , n is the number of repetitions of the repeating unit in the brackets of the molecular formula. The average degree of polymerization of the polyvinyl alcohol of the present invention is 1400 to 2500. Preferably, the degree of hydrolysis of the polyvinyl alcohol is ≥87%.

[0015] Hydroxypropyl methylcellulose, also known as hydroxypropyl methylcellulose and 2-hydroxypropyl ether methylcellulose, is a semi-synthetic product that can be prepared by two methods: (1) treating cotton linter or wood pulp fiber with caustic soda, and then reacting with monoaminomethane and propylene oxide in sequence, refining, and crushing to obtain it; (2) treating a suitable grade of methylcellulose with sodium hydroxide, and reacting with propylene oxide under high temperature and high pressure to an ideal degree, and then refining to obtain it. The molecular weight range of the hydroxypropyl methylcellulose described in the present invention is 1×10 4 ~2×10 5 Da, the substituted methoxy content of the hydroxypropyl methylcellulose is 19-30%, and the substituted hydroxypropyl content is 4-12%.

[0016] Polyethylene glycol borate is synthesized using boric acid and polyethylene glycol as raw materials and benzene as an azeotropic agent for water.

[0017] Preferably, the mass concentration of the water-soluble polymer material in the treatment solution is 0.1-0.2%. Within this range, the bending resistance of the formed foil is improved more effectively.

[0018] The present invention also provides a method for preparing a bending-resistant chemical foil, wherein the chemical foil is treated with a treatment liquid so that a polymer film layer is formed on the surface of the chemical foil; the treatment liquid comprises a water-soluble polymer material, and the water-soluble polymer material is selected from one or more of polyethylene glycol, polyvinyl alcohol, hydroxypropyl methylcellulose or polyethylene glycol borate; the mass concentration of the water-soluble polymer material in the treatment liquid is 0.1-0.7%.

[0019] Preferably, the treatment is to immerse the chemically formed foil in a treatment solution, take it out, and dry it.

[0020] Preferably, the soaking time is at least 2 minutes. The inventors have found in experiments that a soaking time of ≥ 2 minutes can better form a polymer film layer and improve the bending resistance of the chemically formed foil.

[0021] More preferably, the soaking time is 2 to 5 minutes. The inventors have found through research that when the soaking time is greater than 5 minutes, the improvement in the bending resistance of the formed foil is substantially the same as soaking for 5 minutes. Therefore, in order to save processing time, the soaking time is preferably 2 to 5 minutes.

[0022] Preferably, the soaking temperature is 25 to 80° C. More preferably, the soaking temperature is 25 to 70° C.

[0023] Preferably, the chemically-formed foil of the present invention can be a purchased finished chemically-formed foil, or a chemically-formed foil prepared according to an existing conventional method. More specifically, the chemically-formed foil can be obtained by subjecting an etched foil to a chemically-formed treatment, or by subjecting an etched foil to a chemically-formed treatment and washing, or by subjecting an etched foil to a chemically-formed treatment, washing, and drying.

[0024] Preferably, the drying temperature is 100-200°C.

[0025] Preferably, when the chemically formed foil is a low-pressure chemically formed foil, the present invention provides a method for preparing the low-pressure chemically formed foil as a reference: taking a low-pressure corrosion foil and subjecting it to chemical treatment, and then washing it with water, the foil is obtained; wherein, the foil can be dried after washing, and can be stored or sold after drying.

[0026] Preferably, the chemical formation treatment includes a first-stage chemical formation treatment, a passivation treatment, a heat treatment, and a second-stage chemical formation treatment.

[0027] Preferably, the first stage chemical treatment is: taking the low-pressure corrosion foil and placing it in an electrolyte, performing the first stage chemical treatment, and washing with water. In the present invention, reference can be made to the electrolyte commonly used in the first stage chemical treatment in the existing low-pressure chemical foil preparation method, including but not limited to an aqueous solution of adipic acid salt with a mass concentration of 3-15%.

[0028] Furthermore, the first stage formation temperature is 65-95°C, and the current density is 20-25 mA / cm 2 The formation time is 18 to 22 minutes.

[0029] Preferably, in the present invention, the passivation treatment can be performed by referring to the existing low-pressure chemical foil preparation method. The solution used in the passivation treatment is a phosphoric acid aqueous solution with a mass concentration of 1 to 8%; the temperature of the passivation treatment is 50 to 80°C.

[0030] Preferably, the heat treatment is performed at a temperature of 300 to 550° C. and for a time of 1 to 5 minutes.

[0031] Preferably, the second stage chemical formation treatment is: placing the heat-treated corroded foil in an electrolyte for second stage chemical formation. In the present invention, reference may be made to the electrolyte commonly used in the second stage chemical formation treatment in the existing low-pressure chemical foil preparation method, including but not limited to a 0.1-2% mass concentration of ammonium dihydrogen phosphate aqueous solution.

[0032] Preferably, the second stage formation temperature is 50-95°C, and the current density is 20-25 mA / cm 2 The formation time is 4 to 6 minutes.

[0033] The invention also provides a bending-resistant chemical foil, comprising a chemical foil and a polymer film layer coated on the surface of the chemical foil; the polymer film layer is selected from one or more of polyethylene glycol, polyvinyl alcohol, hydroxypropyl methylcellulose or polyethylene glycol borate.

[0034] Additionally, the present invention provides an aluminum electrolytic capacitor, comprising the flexure-resistant forming foil of the present invention.

[0035] The present invention has the following beneficial effects:

[0036] The present invention provides an application of a treatment liquid as an additive for improving the bending resistance of a chemical foil and a method for preparing a bending-resistant chemical foil. The chemical foil is treated with a treatment liquid containing a specific mass concentration and a specific type of water-soluble polymer material. A smooth polymer film can be formed on the surface of the treated chemical foil, thereby reducing the brittleness of the chemical foil, greatly improving the bending resistance of the chemical foil and maintaining the high specific volume of the chemical foil. The chemical foil treated by the treatment method of the present invention has better application value in the actual capacitor production process. DETAILED DESCRIPTION

[0037] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0038] The normal temperature of the present invention is 25-35°C.

[0039] In the specific examples and comparative examples of the present invention, polyethylene glycol xxx, the following "xxx" represents the average molecular weight of polyethylene glycol.

[0040] In Examples 1 to 8 and Comparative Examples 1 to 3, the chemically formed foils were prepared according to the following steps:

[0041] S1. Chemical treatment:

[0042] S11. First stage chemical treatment: the corroded foil is placed in a 15% mass concentration of adipic acid aqueous solution for first stage chemical treatment, and then washed with water; the first stage chemical treatment temperature is 75°C and the current density is 20mA / cm 2 , the formation time is 18min;

[0043] S12. Phosphoric acid passivation treatment: The aluminum foil after the first stage chemical treatment is placed in a phosphoric acid aqueous solution having a mass concentration of 1% for phosphoric acid passivation treatment at a temperature of 50°C;

[0044] S13. Heat treatment: The aluminum foil after phosphoric acid passivation treatment is placed in a drying oven and heat treated at 450°C for 3 min in an air atmosphere;

[0045] S14. Second stage chemical treatment: The heat-treated aluminum foil is placed in a 2% ammonium dihydrogen phosphate aqueous solution for second stage chemical treatment; the second stage chemical treatment temperature is 75°C and the current density is 20 mA / cm 2 , the formation time is 4min;

[0046] S2. Take the corroded foil after the chemical treatment in S1 and wash it with water to obtain the chemical foil.

[0047] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0048] Example 1

[0049] The formed foil was placed in a 0.1% polyethylene glycol 100000 aqueous solution, immersed at room temperature for 3 minutes, and dried at 150°C.

[0050] Example 2

[0051] The formed foil was placed in a 0.1% polyethylene glycol 100000 aqueous solution, immersed at 50° C. for 3 minutes, and dried at 150° C.

[0052] Example 3

[0053] The formed foil was placed in a 0.2% polyethylene glycol 8000 aqueous solution, immersed at 50° C. for 3 minutes, and dried at 150° C.

[0054] Example 4

[0055] The formed foil was placed in a 0.7% polyethylene glycol 8000 aqueous solution, immersed at 50° C. for 2 minutes, and dried at 150° C.

[0056] Example 5

[0057] The formed foil is placed in a polyvinyl alcohol aqueous solution with a mass concentration of 0.1%, immersed at room temperature for 3 minutes, and dried at 150° C. The polyvinyl alcohol is PVA-124, and the average polymerization degree is 2400-2500.

[0058] Example 6

[0059] The formed foil was placed in a 0.1% hydroxypropyl methylcellulose aqueous solution at room temperature for 3 minutes and then dried at 150° C. The hydroxypropyl methylcellulose was purchased from Merck Company with a product number of 423238.

[0060] Example 7

[0061] The formed foil was placed in a 0.1% hydroxypropyl methylcellulose aqueous solution at 70° C. for 3 minutes and dried at 150° C. The hydroxypropyl methylcellulose was purchased from Merck Company with a product number of 423173.

[0062] Example 8

[0063] The formed foil was placed in a polyethylene glycol borate aqueous solution with a mass concentration of 0.1%, immersed at room temperature for 5 minutes, and dried at 150°C.

[0064] The synthesis method of polyethylene glycol borate is as follows: polyethylene glycol 35000 and boric acid are mixed in a molar ratio of 3:1, and reacted at 130°C for 60 minutes in the presence of an azeotropic agent V (benzene) / (water) = 1.25 to obtain the product.

[0065] Comparative Example 1

[0066] The formed foil was placed in a 1% polyethylene glycol 100000 aqueous solution, immersed at 50° C. for 3 minutes, and dried at 150° C.

[0067] Compared with Example 2, the difference is that the mass concentration of polyethylene glycol 100,000 in the polyethylene glycol 100,000 aqueous solution is different, and the mass concentration in this comparative example is 1%.

[0068] Comparative Example 2

[0069] The formed foil was placed in a 0.05% polyethylene glycol 100000 aqueous solution, immersed at 50° C. for 3 minutes, and dried at 150° C.

[0070] Compared with Example 2, the difference is that the mass concentration of polyethylene glycol 100,000 in the polyethylene glycol 100,000 aqueous solution is different, and the mass concentration in this comparative example is 0.05%.

[0071] Comparative Example 3

[0072] The formed foil was placed in a 0.1% polyaluminium sulfate aqueous solution, immersed at 50°C for 3 minutes, and dried at 150°C.

[0073] Compared with Example 2, the difference is that in this comparative example, the polyethylene glycol aqueous solution with a mass concentration of 0.1% is replaced by a polyaluminum sulfate aqueous solution with a mass concentration of 0.1%.

[0074] The molecular formula of polyaluminium sulfate is [Al2(OH) m (SO4) 3- ] n , purchased from MacLean Reagent, product number: A909371.

[0075] Comparative Example 4

[0076] A method for preparing a chemically formed foil comprises the following steps:

[0077] S11. Chemical treatment:

[0078] S111. First stage chemical treatment: the corroded foil is placed in a 15% mass concentration of adipic acid aqueous solution for first stage chemical treatment, and then washed with water; the first stage chemical treatment temperature is 75°C and the current density is 20mA / cm 2 , the formation time is 18min;

[0079] S112. Phosphoric acid passivation treatment: The aluminum foil after the first stage chemical treatment is placed in a phosphoric acid aqueous solution with a mass concentration of 1% for phosphoric acid passivation treatment at a temperature of 50°C;

[0080] S113. Heat treatment: The aluminum foil after phosphoric acid passivation treatment is placed in a drying oven and heat treated at 450°C for 3 min in an air atmosphere;

[0081] S114. Second stage chemical treatment: The heat-treated aluminum foil is placed in a 2% ammonium dihydrogen phosphate aqueous solution for second stage chemical treatment to obtain a chemically formed foil; the second stage chemical treatment temperature is 75°C and the current density is 20 mA / cm 2 , the formation time is 4min;

[0082] S12. Take the corroded foil after the chemical treatment in S11, wash it with water, and then dry it at 150°C to obtain the chemical foil.

[0083] This comparative example is a chemically formed foil obtained by conventional water washing and drying steps after chemically formed foil chemical treatment.

[0084] Performance Testing

[0085] Experimental materials: chemically formed foils obtained by treatment according to the treatment methods of Examples 1 to 8 and Comparative Examples 1 to 3, and chemically formed foil prepared in Comparative Example 4.

[0086] The specific volume and flexural strength of the formed foil are tested. The specific test method or process is as follows:

[0087] Specific capacity: The test was carried out in accordance with the method of electrode foil for aluminum electrolytic capacitors in T / CECA22-2017 group standard of China Electronic Components Industry Association. The test conditions were as follows: electrostatic capacitance tester: measurement accuracy ±2%, test frequency: 120±5HZ, measurement voltage 21V, measurement tank: 500mL glass cup, thermometer: range 100℃, accuracy ±1℃, pure water: 1000mL, ammonium adipate: 150g (capacitance grade), resistivity: 6.5Ω·cm / 70±2℃, pH: 6.7.

[0088] Flexural strength: Tested in accordance with the method of T / CECA22-2017 Electrode foil for aluminum electrolytic capacitors in the group standard of China Electronic Components Industry Association, the test tensile speed is 10±1mm / min, and the tensile force at break is measured in N / cm.

[0089] The test results are shown in Table 1 below. From the data of Examples 1 to 8 and Comparative Example 4 in Table 1, it can be seen that the treatment method provided by the embodiment of the present invention can significantly increase the bending strength of the chemical foil. Compared with Comparative Example 4 (immersed in pure water), the bending strength of the chemical foil obtained by the treatment of the present invention is improved by 13.33% to 21.67%, and the specific volume of the chemical foil is not significantly changed compared with Comparative Example 4. The above results show that the treatment method of the present invention can significantly improve the bending strength of the chemical foil without damaging its specific volume. The prepared chemical foil has better application value in the actual capacitor production process.

[0090] The mass concentration of polyethylene glycol added in Comparative Example 1 is too high. Although the bending strength of the chemically formed foil finally obtained is equivalent to that of the embodiment, its specific volume is significantly reduced, which is reduced by 6.46% compared with that of Example 2.

[0091] The mass concentration of polyethylene glycol added in Comparative Example 2 is too low, and there is no obvious effect on improving the flexural strength of the chemically formed foil. The final flexural strength of the chemically formed foil is only 63N / cm, which is 11.26% lower than that of Example 2 and is basically the same as that of Comparative Example 4 (pure water treatment).

[0092] Comparative Example 3 of the present invention uses different types of high molecular polymer aqueous solutions to soak the chemical foil, but ultimately not only fails to improve the bending strength of the chemical foil, but also significantly reduces its specific volume, which is reduced by 23.33% compared with Example 2.

[0093] Table 1 Test results of specific volume and tortuosity of the chemically formed foils after treatment in various embodiments and comparative examples

[0094] Group <![CDATA[Specific capacitance (μF / cm 2 )]]> Flexural strength (N / cm) Example 1 91.7 70 Example 2 91.3 71 Example 3 91.2 73 Example 4 91.0 68 Example 5 91.2 72 Example 6 91.2 72 Example 7 91.5 73 Example 8 91.4 72 Comparative Example 1 85.4 73 Comparative Example 2 91.1 63 Comparative Example 3 70 60 Comparative Example 4 91.2 60

[0095] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. The use of the treatment liquid as an additive for improving the bending resistance of the chemically formed foil is characterized in that: The treatment liquid comprises a water-soluble polymer material, and the water-soluble polymer material is selected from one or more of polyethylene glycol, polyvinyl alcohol, hydroxypropyl methylcellulose or polyethylene glycol borate; the mass concentration of the water-soluble polymer material in the treatment liquid is 0.1-0.7%.

2. The application according to claim 1, characterized in that: The mass concentration of the water-soluble polymer material in the treatment liquid is 0.1-0.2%.

3. A method for preparing a bending-resistant chemically formed foil, characterized in that: The chemical foil is treated with a treatment liquid to form a polymer film layer on the surface of the chemical foil; the treatment liquid includes a water-soluble polymer material, and the water-soluble polymer material is selected from one or more of polyethylene glycol, polyvinyl alcohol, hydroxypropyl methylcellulose or polyethylene glycol borate; the mass concentration of the water-soluble polymer material in the treatment liquid is 0.1-0.7%.

4. The preparation method according to claim 3, characterized in that: The treatment comprises immersing the chemically formed foil in a treatment solution, taking it out, and drying it.

5. The preparation method according to claim 4, characterized in that: The soaking time is at least 2 minutes.

6. The preparation method according to claim 4, characterized in that: The soaking temperature is 25-80°C.

7. The preparation method according to claim 4, characterized in that: The drying temperature is 100-200°C.

8. The preparation method according to claim 3, characterized in that: The chemically formed foil is obtained by subjecting the corrosion foil to chemical treatment, or by subjecting the corrosion foil to chemical treatment and water washing, or by subjecting the corrosion foil to chemical treatment, water washing and drying.

9. A flex-resistant foil, characterized in that: The invention comprises a chemical foil and a polymer film layer coated on the surface of the chemical foil; the polymer film layer is selected from one or more of polyethylene glycol, polyvinyl alcohol, hydroxypropyl methylcellulose or polyethylene glycol borate.

10. An aluminum electrolytic capacitor, characterized in that: The invention comprises the bending-resistant formed foil prepared by the preparation method according to any one of claims 3 to 8 or the bending-resistant formed foil according to claim 9.

Citation Information

Cited By

  • Medium-high voltage formed foil and manufacturing method thereof

    CN120824128A